Sorting using heap structure - Alam Chowdhury, Rezaul; Kaykobad, M. (International journal of computer mathematics, 2001)
In this paper we present a new sorting algorithm for heaps which can sort n (=2 h+1 - 1) elements using no more than nlog 2 (n+1) - (13/12)n - 1 element comparisons in the worst case 2 (including the heap creation phase). Experimental results show that this algorithm requires only nlog 2 (n+1) - 1.2n element comparisons in the average case. However it requires extra space for 2 n LINK fields